Methodological problems of determining the concept of legal consciousness as a category of philosophy and a legal phenomenon - Vershok, Irina L. (Journal of the Belarusian State University. Law, 2020)
The article is devoted to the revision of the term «legal consciousness» with the aim of overcoming the emerging semantic devaluation that occurred as a result of its frequent application and blurring of semantic boundaries by establishing its clear boundaries and the context of use. The object of research is legal consciousness as a philosophical category and a legal phenomenon. The purpose is to overcome the semantic devaluation of the term «legal consciousness». As a result of the research using a new for jurisprudence nominalist approach, as well as linguistic and psychological methods, the semantic limitation of the concept and category of legal consciousness is substantiated. Legal consciousness is recognized as a philosophical, worldview meta-scientific category used in the search for ideal forms of state and legal construction, in which legal consciousness manifests is a static phenomenon. Along with this, the scientific study of the concept and category of legal consciousness as a legal phenomenon, manifested in legal behaviour at the collective as well as at the individual level, is substantiated. This implies the need to study legal consciousness both at an extremely high and at a low level of generalization. The significance of the results of the research: a new direction is being laid for further studies of legal consciousness in its dynamics and with a contextual predetermination of interpretation: separately at the level of fundamental research, as well as at the level of applied sciences. The proposals developed at the fundamental level will help to identify trends in the transformation of legal consciousness and its consequences for the legal system, and at the applied level, to develop mechanisms to ensure coherence and intentionality of law subjects’ legal consciousness.
Keywords: dynamics of legal consciousness; internal and external imperative of legal consciousness; intentionality of legal consciousness; tension of legal consciousness